Helping Feed the World with Rice Innovations: RICE Research Adoption and Impact on Farmers Globally - CGIAR Research Program on Rice (2021)
The study found that stress-tolerant varieties in Asia and New Rice for Africa (NERICA) varieties in Africa had a significant impact on rice yield and income. Additionally, institutional innovations, training, and natural resource management practices, such as direct-seeded rice, rodent control, and iron-toxicity removal, have a considerable effect on smallholder rice farmers? economic well-being (income and rice yield). Given the important uptake of stress-tolerant varieties documented in Latin America, additional positive impacts are expected.